Slovene musical terminology in textbooks between past and present - Grazio, Jelena (Array, 2019)
The aim of this paper is to present the most important issues of the Slovene music terminology in the field of teaching music theory. The examples chosen tackle the problem of equating two or more terms with different meanings (e.g. G-clef and treble clef, chord and triad, terms that refer to patterns of accents and beats). The hypothesis of this paper is that the lack of any clear separation between terms and concepts is misleading for readers and possibly counterproductive in understanding the material. The chosen examples illustrate the link between synonymy and polysemy on one hand and terminological inconsistencies on the other.